Electrical Bioimpedance as a Detection Tool for Internal Hemorrhaging and Blood Aggregation - Morse, John (Université d'Ottawa / University of Ottawa, 2014)
Electrical bioimpedance was used to detect local volume and aggregation changes in blood. This was done with two separate experimentation processes to improve upon current research methods. Abdominal internal hemorrhaging is bleeding and pooling of blood within the abdominal cavity which can put the welfare of the patient at risk and may cause organ failure. Electrical bioimpedance is the response of biological tissue to applied electrical current. In cooperation with Bioparhom, electrical bioimpedance was used as a detection device for abdominal internal hemorrhaging. It is hypothesized that electrical bioimpedance could be a non-invasive and cost effective avenue for the detection of internal bleeding. In this study we investigate the use of electrical bioimpedance with a custom 8x8 needle electrode array, for detecting and locating the blood pooling due to a drop in resistivity in a rat using a Z-Metrix (function generator by Bioparhom). 5 and 95 kHz signals were inputted into a dead rat experiencing internal bleeding of porcine blood at a rate of 3.33 ml/min to 10 ml. For 8 rats, the 5 kHz frequency was found to be more sensitive to internal blood pooling. Red blood cell aggregation is a physiological process where red blood cells form reversible aggregates. RBC aggregation is an important indicator for physicians for the health of the circulatory system. Utilizing electrical bioimpedance, it is hypothesized that a reactance change as a result of blood aggregation will be detected. As well, a method is developed using impedance spectroscopy to determine s frequency which exhibits the highest reactance change during blood aggregation. This sensitive frequency, found to be 304 kHz, is compared to a frequency used by previous studies (100 kHz) to validate its. Using the Z-Metrix (function generator by Bioparhom) with a custom 4 electrode configuration, 2 ml of porcine blood mixed with 2 mg/ml of EDTA is tested for 2 minutes at a single frequency. The 304 kHz is found to be the most sensitive of the frequencies tested to reactance changes during aggregation. Results found for blood samples give an average AIc of 27.32 ± 11.44, which is within the physiological range for porcine blood of 3-30. It is seen that the 304 kHz has a higher precision than the 100 kHz frequency, but the AIc is within the same magnitude. As a result, 304 kHz is found to be a more favorable frequency than the previously published 100 kHz for the trials performed based on precision of the results and the sensitivity of the reactance change to blood aggregation.
Keywords: Electrical Bioimpedance; Internal Hemorrhaging; Blood Aggregation